Private-Law Status of a Higher Education Institution - MAKAROV, Timofey G.; KOBCHIKOVA, Elena V.; CHEPARINA, Olga A.; BARABANOVA, Svetlana V.; NASONKIN, Vladimir V. (Journal of Advanced Research in Law and Economics; Vol 7 No 2 (2016): JARLE, Volume VII, Issue 2(16), Spring 2016, 2016)
The importance of the research topic is determined by the fact that the private-law elements are observed to actively penetrate into higher education. Hence, the legal status of a higher education institution undergoes drastic changes. Its conventional public-law elements start combining with private-law elements specific to market relations. The private-law status of a higher education institution includes its private legal personality, rights and duties within civil circulation, and private-law responsibility. The purpose of this research is to provide a comprehensive scientific insight into the private-law status of a higher education institution, the elements of such status, and the interrelation among such elements. The main method used to study the problem of identifying the private-law status of a higher education institution is method of analyzing laws and regulations, as well as the sources of literature devoted to the civil regulatory matters of higher education. It is found that the private-law status of a higher education institution comprises its private legal personality, rights and duties within civil circulation, and its private-law responsibility for non-performing the relevant duties. It is shown that within the system of education, including higher education, private-law elements develop actively. Hence, the private-law elements expand in the private-law status of higher education institutions. The results of this study are of practical relevance for civilists specializing in education law and for lawyers working at higher education institutions.